Paragonimiasis in School Children from Condebamba Valley, Cajamarca - Peru - Cornejo Medina, William (1999)
OBJECTIVE: To assess the prevalence of paragonimosis among elementary school students from three villages of Condebamba valley, Cajamarca - Perú. MATERIAL AND METHODS: 77 school-age children underwent parasitologic examination in stools, skin test and counterimmunoelectrophoresis in those positive for skin reactivity. RESULTS: From 77 skin tests performed, 2 were positive (2,6%), which were also positive by counterimmunoelectrophoresis. All 77 stool samples were negative for Paragonimus eggs. CONCLUSION: These results showed a decreasing prevalence of human paragonimiasis among Condebamba valley children.